2018
DOI: 10.3390/s18103260
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Distributed Microfabricated Strain Gauges on Stretchable Sensor Networks for Structural Applications

Abstract: Smart structures mimic biological systems by using thousands of sensors serving as a nervous system analog. One approach to give structures this sensing ability is to develop a multifunctional sensor network. Previous work has demonstrated stretchable sensor networks consisting of temperature sensors and impact detectors for monitoring external environments and interacting with other objects. The objective of this work is to develop distributed, robust and reliable strain gauges for obtaining the strain distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The effectiveness and accuracy of this stretchable network is the important first step toward “fly‐by‐feel” aerospace vehicles. Chen et al developed a distributed strain gauge network for obtaining the strain distribution of a designated region on a target structure . This stretchable network had 27 strain gauges, 6 temperature devices, and 8 piezoelectric transducers.…”
Section: Applications Of Fhementioning
confidence: 99%
“…The effectiveness and accuracy of this stretchable network is the important first step toward “fly‐by‐feel” aerospace vehicles. Chen et al developed a distributed strain gauge network for obtaining the strain distribution of a designated region on a target structure . This stretchable network had 27 strain gauges, 6 temperature devices, and 8 piezoelectric transducers.…”
Section: Applications Of Fhementioning
confidence: 99%
“…Moreover, the sensing sheet and dedicated data acquisition system were deployed on a concrete bridge for a several-hour-long field test. Other studies on the development of large-area sensor arrays have demonstrated capacitive sensors [ 15 , 16 ] and sensor arrays that utilize lead zirconate titanate (PZT) piezoelectric sensors [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in connection with the measurement of the angle of rotation, the strain gauge is used as a measuring element in [ 12 ]. Progressive methods include the placement of strain gauges in networks, as reported in [ 20 ]. In this case, also in cooperation with other sensors, such as thermometers and piezoelectric elements.…”
Section: Introductionmentioning
confidence: 99%